Adsorption of Cu(II) Ions onto a Cellulosic Biosorbent, Leaf Powder: Application in Water Treatment - Krishna Gopal Bhattacharyya; Arunima Sarma; Jyotirekha Sarma (Adsorption Science & Technology)
In the present work, Azadirachta indica (neem) leaves were converted to a powder for use in the separation of Cu(II) ions from water. The powdered biomass was investigated as a sorbent for Cu(II) ions employing pH, time, initial Cu(II) ion concentration and the amount of sorbent as the experimental variables. At very low pH, Cu(II) ions were incapable of competing effectively with H + ions for the sorption sites, but at the natural pH (5.6) of the aqueous Cu(II) ion solution up to 90% of the Cu(II) ions could be separated by sorption onto 4 g of Azadirachta indica leaf powder (AILP) from an aqueous solution of 50 mg/ℓ concentration. The experimental data were well fitted by the Langmuir and Freundlich isotherm equations and followed pseudo-second-order kinetics. The Langmuir monolayer capacity of AILP for Cu(II) ions was 6.7–33.3 mg/g, which could be considered as reasonable. Azadirachta indica leaf powder could be a very effective sorbent for Cu(II) ions from an aqueous medium. The cellulosic units present in AILP provide a matrix of OH − , COO − , CN − and other anions that bind Cu(II) ions to the surface. The process was exothermic with ΔH 0 values of −96.1 kJ/mol to −105.4 kJ/mol, reflecting the strong Cu(II)–AILP linkages formed. This was supported by an appropriate increase in the standard entropy change and a decrease in the Gibbs' free energy.